Ethnobotanical survey of plants used some respiratory diseases - P. Sundaramoorthy, D. Vijay, K. Sankar Ganesh (Recent Research in Science and Technology, 2009)
India is called Ã¢â‚¬Å“Botanical Garden of the WorldÃ¢â‚¬Â as it is having the highest number of medicinal herbs.Ã‚Â  Out of more than 25000 plants, only 10% of the plants are used for their medicinal values. Ayurvedic is one of the most ancient systems of medicines in the world.Ã‚Â  Ayurvedic medicines are considered to be the best systems of treatment in India and this system is spreading now globally.Ã‚Â  Natural products are also a part of our everyday life.Ã‚Â  Right from the inception, India has a rich heritage of usage of Ayurvedic and Herbal medicines supported by neutraceuticals.Ã‚Â Ã‚Â  Respiratory diseases are the term used for diseases found related to the respiratory system due to air contamination, i.e., Cough, Cold, Expectorant, Asthma etc., In order to get information regarding the treatment, a survey was made with village people suffering from respiratory infections and cured by using herbal Medicine.Ã‚Â Ã‚Â 